The first four years eaudiobook - Wilder, Laura Ingalls (Little House, 2017)
Laura Ingalls Wilder is beginning life with her new husband, Almanzo, in their own little house. Laura is a young pioneer wife now, and must work hard with Almanzo, farming the land around their home on the South Dakota prairie. Soon their baby daughter, Rose, is born, and the young family must face the hardships and triumphs encountered by so many American pioneers. And so Laura Ingalls Wilder's adventure as a little pioneer girl ends, and her new life as a pioneer wife and mother begins. The nine Little House books have been cherished by generations of readers as both a unique glimpse into America's frontier past and a heartwarming, unforgettable story. Correlates to the Common Core State Standards in English Language Arts.